2018
DOI: 10.1590/1980-5373-mr-2018-0134
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite Films Based on Flaxseed Gum and Cellulose Nanocrystals

Abstract: Flaxseed gum (FG)-based films were developed with the addition of glycerol as a plasticizer and glutaraldehyde as a crosslinking agent. HCl was added to improve crosslinking and decrease the hydrophilicity of the matrix. Different cellulose nanocrystal (CN) amounts were used as reinforcements in the optimum FG formulation. The crosslinking process at pH 3.5 led to a lower solubility of FG in water (from 100% to 53%) and an increase in thermal stability (from 160 ºC to 209 ºC). FTIR analysis confirmed a reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Particularly, in recent decades, many researches have been carried out to develop polymer nanocomposites and much attention has been focused on the addition of natural fiber nanocellulose as a reinforcement phase. This is mainly due to the current interest and need for development of sustainable products [1,3]. Cellulose nanocrystals show competitive advantages over synthetic industrialized materials, commonly used today as composites reinforcement, as they are renewable and biodegradable [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, in recent decades, many researches have been carried out to develop polymer nanocomposites and much attention has been focused on the addition of natural fiber nanocellulose as a reinforcement phase. This is mainly due to the current interest and need for development of sustainable products [1,3]. Cellulose nanocrystals show competitive advantages over synthetic industrialized materials, commonly used today as composites reinforcement, as they are renewable and biodegradable [3].…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly due to the current interest and need for development of sustainable products [1,3]. Cellulose nanocrystals show competitive advantages over synthetic industrialized materials, commonly used today as composites reinforcement, as they are renewable and biodegradable [3]. Moreover, cellulose nanocrystals have excellent properties such as low density, high crystallinity and improved physical and mechanical performance, associated with high Young's modulus, high strength and low thermal expansion coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that, compared with films made from pure mucilage, films produced from the blend of FM and polyvinyl alcohol (PVA) (at a ratio of 1:1) exhibited less resistance, less rigidity, more flexibility, high thermal stability, and unaltered water vapor barrier properties [ 67 ]. Prado et al [ 68 ] demonstrated that the degree of water solubility and the swelling of FG-based films were reduced due to the incorporation of cellulose nanocrystals, while the stiffness and tensile strength of the films were remarkably improved. Recently, Yang et al [ 66 ] prepared three-layer FG/chitosan (CS)/FG coatings containing laurel essential oil and eugenol via a casting method, and they were used to preserve the myofibrillar protein in rainbow trout fillets.…”
Section: Food Applications Of Fm/fgmentioning
confidence: 99%
“…The ability of FG in the flotation of fluorite from calcite has been demonstrated [ 90 ]. Together with cellulose nanocrystals, FG may form nanocomposite materials or biopolymers that can be used to produce bioplastics [ 91 ].…”
Section: Flaxseed Gummentioning
confidence: 99%